Pendidikan Pesantren dan Perempuan: Meneladani Sosok KH Abdul Wahab Turcham - Dinar Bela Ayu Naj'ma; Syamsul Bakri; Andi Arif Rifa'i (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study explores the pivotal role of pesantren in advancing women’s education in Indonesia, focusing on KH. Abdul Wahab Turcham in Surabaya. Pesantren, as traditional Islamic educational institutions, have been central to both religious and secular education in Indonesia. This qualitative research uses a descriptive approach and literature review to examine how pesantren are adapting to contemporary educational demands for women. The study emphasizes the need for policy initiatives and community support to transform Islamic boarding schools to meet evolving educational needs. Findings highlight KH. Abdul Wahab Turcham's significant contributions and the challenges female students face, underscoring the Kiai's role in fostering an empowered female generation.